1997
DOI: 10.1152/ajpheart.1997.272.6.h2591
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ceramide in inhibitory effect of IL-1 beta on L-type Ca2+ current in adult rat ventricular myocytes

Abstract: Interleukin (IL)-1 beta has previously been shown to decrease the L-type Ca2+ channel current (ICa,L). Because ceramide has been suggested to mediate many biological effects of IL-1 beta, we examined whether ceramide was involved in the IL-1 beta-induced suppression of ICa,L in adult rat ventricular myocytes. Exposure of myocytes to 5 ng/ml IL-1 beta elicited a 140% increase in ceramide production within 2 min, as measured with 32P phosphorylation. Whole cell patch-clamp techniques were used to measure ICa,L i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 0 publications
4
32
0
1
Order By: Relevance
“…In patch-clamped myocytes, n-ceramide, a naturally occurring ceramide, produced an inhibitory effect on I Ca,L , similar to C 2 -ceramide, as described previously (31). This effect, however, was accompanied by increases in systolic amplitude and the duration of contraction.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In patch-clamped myocytes, n-ceramide, a naturally occurring ceramide, produced an inhibitory effect on I Ca,L , similar to C 2 -ceramide, as described previously (31). This effect, however, was accompanied by increases in systolic amplitude and the duration of contraction.…”
Section: Discussionsupporting
confidence: 74%
“…C 2 -ceramide has also been shown to reduce I Ca,L in these preparations (29,31). The present study demonstrated that despite its reduction in I Ca,L , ceramide induced a positive inotropic effect and an increase in systolic free Ca i 2ϩ , a positive lusitropic effect, and an increase in the Ca 2ϩ sensitivity of contractile proteins.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This characteristic is important because some diets have been shown to alter membrane lipid composition (5,(16)(17)(18). Changes in lipid composition, in particular an alteration in cholesterol and sphingolipids concentrations, may regulate the activity of ion channels and pumps (19)(20)(21). Littermates of the C57BL/6 mice were used as control animals.…”
Section: Micementioning
confidence: 99%